Recess for Students with Visual Impairments - Lucas, Matthew D. (Journal of the American Academy of Special Education Professionals, 2010)
During recess, the participation of a student with visual impairments in terms of movement can often be both challenging and rewarding for the student and general education teacher. This paper will address common characteristics of students with visual impairments and present basic solutions to improve the participation of these students in the recess setting. Initially the definition and prevalence of visual impairments will be presented. This will be followed by a discussion of possible challenges and general solutions for children with visual impairments in the recess setting. Lastly, specific methods of including a student with visual impairments in movement recess activities will be discussed.